Assessment of welfare of finishing beef cattle kept on different types of floor after short- or long-term housing. (25th February 2015) - Brscic, M.; Gottardo, F.; Tessitore, E.; Guzzo, L.; Ricci, R.; Cozzi, G.
Abstract : This study aimed at evaluating short- and long-term effects of housing beef cattle on deep litter (DL) or concrete fully slatted floor (FS) on their welfare. Animal-based measures of the Welfare Quality ® assessment protocol for cattle were used to assess health status and behaviour of bulls. The assessment was carried out in a large commercial farm on 15 batches of bulls (4 DL and 11 FS) 1 month after their receiving day (short-term) and on 12 batches (three DL and nine FS) the week before slaughter (long-term). Signs of better comfort on deep litter in terms of shorter lying down durations (5.1±0.5 v . 6.5±0.4 s; P <0.05) and lower risk of hairless patches (odds ratio=0.09; 95% confidence interval=0.01 to 0.68; P <0.05) were already observed after 1 month. Heavy bulls after a long-term housing on FS showed a higher prevalence of bursitis, hairless patches and lesions/swellings than animals on DL. Bulls on fully slatted floor were at higher risk of early culling (odds ratio=6.44; 95% confidence interval=1.57 to 26.37; P <0.01), mainly due to musculoskeletal system pathologies/lameness. Deep litter proved to be a valid alternative to slatted floor, making animals more confident to interact with powerful movements such as mounting at the end of the finishing period. A negative aspect of the deep litter was the poor cleanliness of the bulls. Compared with the fully slatted floor, there were higher odds ratios for dirty bulls at both, the short- (odds ratio=25.09; 95% confidence interval=8.96 to 70.22; P <0.001) and the long-term housing (odds ratio=276.13; 95% confidence interval=98.21 to 776.38; P <0.001). In order to improve health and welfare of beef cattle finished at a heavy weight, deep litter systems are a promising alternative to fully slatted floors. However, proper management of deep litter is necessary to maintain satisfactory cleanliness of the bulls.